A Study on Intercultural Pragmatic Failure and Development of Intercultural Interactive Competence based on International Chinese Education - Peng, Zhang; Liwen, Chao (Sinología hispánica. China Studies Review, 2024)
Inter-cultural interaction is prevalent within international Chinese education. However, a variety of factors often lead to cross-cultural pragmatic failure and failed interactions. This article studies the practices of international Chinese education and intercultural interaction failure and its factors, aiming to find out how cognitive psychological factor decides and explore strategies of developing students’ cross-cultural interactive competence to reduce failure.